(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The present study aimed at identifying the effect of Ozone on the chemical and physical properties of buffalo milk including the fat, protein, solid materials, lactose, salts, specific weight and pH. the results showed that treating the buffalo milk led to slight changes in the rate of fat content, solid materials, lactose, salts, specific weight and an increase in the viscosity of the milk. when some properties of milk samples were studied, it was observed that there was a slight decrease in the viscosity of the yoghurt samples made from buffalo milk and a decrease in whey osmosis with a rise in pH. after conducting the sensed assessment, the samples of yoghurt had the highest value of appearance and color when the treatment period was (60) minutes, while the treatment of (40) minutes gave the highest value in terms of the flavor and no change was observed in the property of the form for all the periods of exposure to the ozone.